2008
DOI: 10.1007/s11104-008-9708-z
|View full text |Cite
|
Sign up to set email alerts
|

Boron alleviates aluminum toxicity in pea (Pisum sativum)

Abstract: One important target of boron (B) deficiency and aluminum (Al) toxicity is cell wall. Thus we studied the hypothesis that B is capable of alleviating Al toxicity in pea (Pisum sativum). Short-term and prolonged Al exposure to pea roots at different B levels was carried out on uniform seedlings precultured at a low B level. When seedlings with a low B level were supplied with or without B for 1 and 2 days before 24 h Al exposure, roots were longer while root diameter was thinner after B addition especially for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 52 publications
3
46
0
Order By: Relevance
“…Confirming these findings, Jiang et al Role of boron and phosphorous on aluminum toxicity An investigation was conducted (Jiang et al, 2009b) with Citrus grandis L. seedlings to determine how boron alleviates Al-induced inhibition of root and shoot growth and results confirmed that inhibition of root and shoot growth is not due to Al-induced boron deficiency, but due to Al toxicity. Their findings on preventive measures of boron are in line with the results of Yu et al (2009), who conducted a similar study with pea (Pisum sativam). According to Jiang et al (2009b), boron induced changes in Al speciation and/or sub-cellular compartmentation would be the reason behind amelioration of root inhibition in citrus, which has previously stated by Corrales et al (2008) also.…”
Section: Effect Of Aluminum On Citrussupporting
confidence: 83%
“…Confirming these findings, Jiang et al Role of boron and phosphorous on aluminum toxicity An investigation was conducted (Jiang et al, 2009b) with Citrus grandis L. seedlings to determine how boron alleviates Al-induced inhibition of root and shoot growth and results confirmed that inhibition of root and shoot growth is not due to Al-induced boron deficiency, but due to Al toxicity. Their findings on preventive measures of boron are in line with the results of Yu et al (2009), who conducted a similar study with pea (Pisum sativam). According to Jiang et al (2009b), boron induced changes in Al speciation and/or sub-cellular compartmentation would be the reason behind amelioration of root inhibition in citrus, which has previously stated by Corrales et al (2008) also.…”
Section: Effect Of Aluminum On Citrussupporting
confidence: 83%
“…The selected roots were stained by the Yu et al (2009) method. After soaking in a solution of 0.2% hematoxylin and 0.02% KI, the plant roots were washed with de-ionized water until no dye in the rinsing water and studied under stereomicroscope and images were taken with Nikon digital camera.…”
Section: Histochemical Determination Of Al By Hematoxylin Stainingmentioning
confidence: 99%
“…For determination of Al concentrations in leaves and roots (0-10 mm root apices), the roots were washed 3 times with 0.5 mM CaCl 2 solution, and Al concentrations were determined by graphite furnace atomic absorption spectrophotometer (GTA 120 Graphite Tube Atomizer, Agilent Technologies, 200 series AA) as described by Yu et al (2009). B contents in leaves and roots were measured by Dible et al (1954) method.…”
Section: Determination Of Al and B In Root Tips And Leavesmentioning
confidence: 99%
See 2 more Smart Citations